Group photograph of Perkin-Elmer Corporation employees - Perkin-Elmer Corporation (1954)
Group photograph of unidentified employees of the Perkin-Elmer Corporation, a manufacturer of analytical instruments, diagnostic tools, and medical imaging equipment. A copy of The Perkin-Elmer News , an in-house publication, announcing the company's acquisition of a German instrument company (Askania GmbH) is visible at the center of the table.
Keywords: Employees; Perkin-Elmer Corporation; Corporations; Women employees